(untitled) (Jóvenes en la Ciencia, 2024)
During clinical practice it is common to normalize the transfer of anxiety and negative feelings within students, even more so when it is the first time to enter the hospital environment, when it should be a period in which they are with greater emotional stability, to be able to function successfully in this period. Therefore, this article aims to evaluate the degree of anxiety present in students of the Nursing and Midwifery Degree in the third semester of the University of Guanajuato in their first clinical practices. A cross-sectional and retrospective study was carried out, with a total population of 93 participants, to whom the “Beck Anxiety Inventory” (BAI) test was applied. It was shown that there is a higher prevalence of mild anxiety levels in women compared to men. These results suggest that students manifest symptoms of anxiety when facing the hospital environment for the first time.